Pengaruh Persepsi Kemudahan, Lingkungan Sosial dan Literasi Keuangan terhadap Minat Penggunaan QRIS - Zanra, Sri; Sufnirayanti, Sufnirayanti (Penerbit Goodwood, 2024)
Purpose: This research aims to determine the influence of perceived convenience, social environment and financial literacy on interest in using QRIS among MSMEs in Pekanbaru City, moderated by education level. Research methodology: This study is a quantitative research, the data in this research have been acquired form the distribution of questionnaires and use Partial Least Square app technique which data processing was assisted by Smart PLS 3.0. In this research, a sample of 100 people was used. Results: Perception of convenience, social environment and financial literacy have a direct influence on interest in using QRIS among MSMEs in Pekanbaru City. Meanwhile, based on the moderation test, it was concluded that the level of education did not moderate the influence of perceived convenience and social environment on interest in using QRIS among Pekanbaru City MSMEs. However, the level of education is able to moderate the influence of financial literacy on interest in using QRIS among Pekanbaru City MSMEs.. Limitations: The research was conducted with a limited sample, both in terms of sample size and population diversity. This could affect the appropriate representation of the MSME population in Pekanbaru City and may limit the conclusions that can be drawn. Contribution: This research is expected to provide deeper insight into the factors that influence the adoption of QRIS payment technology, as well as the potential role of education level in this process.